The effect of clopidogrel and aspirin on the severity of traumatic brain injury in a rat model. (March 2022) - Kobeissy, Firas; Mallah, Khalil; Zibara, Kazem; Dakroub, Fatima; Dalloul, Zeinab; Nasser, Mohammad; Nasrallah, Leila; Mallah, Zahraa; El-Achkar, Ghewa A.; Ramadan, Naify; Mohamed, Wael; Mondello, Stefania; et al.
Abstract: Traumatic Brain Injury (TBI) is one of the leading causes of death and disability worldwide. Aspirin (ASA) and clopidogrel (CLOP) are antiplatelet agents that inhibit platelet aggregation. They are implicated in worsening the intracerebral haemorrhage (ICH) risk post-TBI. However, antiplatelet drugs may also exert a neuroprotective effect post-injury. We determined the impact of ASA and CLOP treatment, alone or in combination, on ICH and brain damage in an experimental rat TBI model. We assessed changes in platelet aggregation and measured serum thromboxane by enzyme immune assay. We also explored a panel of brain damage and apoptosis biomarkers by immunoblotting. Rats were treated with ASA and/or CLOP for 48 h prior to TBI and sacrificed 48 h post-injury. In rats treated with antiplatelet agents prior to TBI, platelet aggregation was completely inhibited, and serum thromboxane was significantly decreased, compared to the TBI group without treatment. TBI increases UCHL-1 and GFAP, but decreases hexokinase expression compared to the non-injured controls. All groups treated with antiplatelet drugs prior to TBI had decreased UCH-L1 and GFAP serum levels compared to the TBI untreated group. Furthermore, the ASA and CLOP single treatments increased the hexokinase serum levels. We confirmed that αII-spectrin cleavage increased post-TBI, with the highest cleavage detected in CLOP-treated rats. Aspirin and/or CLOP treatment prior to TBI is a double-edged sword that exerts a dual effect post-injury. On one hand, ASA and CLOP single treatments increase the post-TBI ICH risk, with a further detrimental effect from the ASA + CLOP treatment. On the other hand, ASA and/or CLOP treatments are neuroprotective and result in a favourable profile of TBI injury markers. The ICH risk and the neuroprotection benefits from antiplatelet therapy should be weighed against each other to ameliorate the management of TBI patients. Highlights: ASA and/or CLOP treatment prior to TBI is a double-edged sword that exerts a dual effect post-injury. ASA, CLOP, and ASACLOP treatments increase the post-TBI ICH risk. ASA, CLOP and ASACLOP treatments are neuroprotective with favourable profiles of TBI injury markers. ASACLOP treatment is the most potent in inhibiting platelet aggregation and decreasing serum-TXB2 post-TBI. UCHL-1, GFAP, and hexokinase expression levels are restored to pre-injury levels by antiplatelet drugs.